2022
DOI: 10.3390/medicines10010003
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Mesenchymal Stem Cells and Their Secretomes in Decreasing Inflammation Markers in Polycystic Ovary Syndrome Treatment: A Systematic Review

Abstract: Background: Polycystic ovary syndrome (PCOS) is a chronic disorder and is one of the most common endocrine disorders in women of a reproductive age. The prevalence of PCOS is growing globally; 52% of women in Southeast Asia alone suffer from this disorder. This disorder is caused by chronic hyperandrogenism, which hinders folliculogenesis. There is also a close relationship between hyperandrogenism and hyperinsulinemia/insulin resistance (IR), and it is estimated that 40–80% of PCOS patients suffer from insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“… 18 miRNAs can be engaged in the development of PCOS by regulating insulin sensitivity, androgen synthesis, and follicular development. 19 Such as miR-182, 20 miR-664a-3p, 21 and miR-24. 22 MiR-379 is identified as an obesity-associated miRNA that regulates the development of obesity through multiple signaling pathways or metabolic modalities, thereby influencing the development of disease.…”
Section: Discussionmentioning
confidence: 99%
“… 18 miRNAs can be engaged in the development of PCOS by regulating insulin sensitivity, androgen synthesis, and follicular development. 19 Such as miR-182, 20 miR-664a-3p, 21 and miR-24. 22 MiR-379 is identified as an obesity-associated miRNA that regulates the development of obesity through multiple signaling pathways or metabolic modalities, thereby influencing the development of disease.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs have therapeutic significance through the capability to divide into diverse cell lineages and influence immune responses through the modulation of the immune system. MSCs have been found to reactivate endometrial function and enhance the outcomes of pregnancy 15 - 17 .…”
Section: Regenerative Medicine: Stem Cell Therapymentioning
confidence: 99%
“…This effect is mediated by growth factors and suppressive cytokines, which regulate and eventually reduce the inflammatory process. In research provided by Zhao et al, they reported the anti-inflammatory effect presented in UC-MSC-derived exosomes specifically on the granulosa cells in the follicular fluid of the PCOS patients, and it was discovered that TNF-α and interferon-gamma (IFN-γ) were significantly decreased and that IL-10 levels were increased in the PCOS patients [ 61 ].…”
Section: Application Of Mesenchymal Stem Cells In Gynecological Disor...mentioning
confidence: 99%
“…exosomes specifically on the granulosa cells in the follicular fluid of the PCOS patients, and it was discovered that TNF-α and interferon-gamma (IFN-γ) were significantly decreased and that IL-10 levels were increased in the PCOS patients [61].…”
Section: Primary Ovarian Insufficiency (Poi)mentioning
confidence: 99%